The Influence of Using Learning Modules on Students' Cognitive Learning Outcomes in Educational Management - Sherly; Eka Nadya (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Learners are the main and most important resource in the process of formal education. The existence of students is not just meeting their needs but is part of the quality of educational institutions. This means that quality student management is needed for these educational institutions so that students can grow and develop according to their physical condition and intellectual intelligence. Most students face many difficulties in solving problems given by the teacher, even though the information is clear and complete, while the teacher faced difficulties in educating participants to find ways to solve problems well. To be able to solve the problem properly, several things are necessarily considered including time spent on problem-solving, lesson planning, and learning resources needed. Thus expected application of the Somatic Auditory Visualization Intellectual learning model (SAVI). combined with teaching aids will further add to the variety of learning models that are more interesting, increase the activity and cooperation of students and improve students' problem-solving abilities.